Una nueva domesticidad. Los indígenas de la Alta California y la vivienda misional - Catherine R. Ettinger (Nuevo mundo - Mundos Nuevos, 2010)
The Christianization of the native population of Alta California in the 18th century –as in other parts of Iberian America- implied the modification of spatial structures. This paper deals specifically with the case of the restructuring of domestic space in relation to the desire to make the native population in this peripheral territory more European. Through the voices of the different social actors --explorers, commanders, friars and natives-- different perspectives on domestic space and its modification are examined. I argue that the Franciscan friars were aware of the role that space, in general, and domestic space, in particular, played in the project of Christianization of the native population and their transformation into European subjects.